Impact of Neutrophil Extracellular Traps on Thrombosis Formation: New Findings and Future Perspective - Zhou, Yilu; Xu, Zhendong; Liu, Zhiqiang (Frontiers in Cellular and Infection Microbiology, 2022)
Thrombotic diseases seriously endanger human health, neutrophils and neutrophil extracellular traps (NETs) play an important role in abnormal thrombus formation. NETs are extracellular structures released by neutrophils upon stimulation by pathogens. NETs include neutrophil elastase (NE), myeloperoxidase (MPO), cathepsin G and other active substances. The network structure provided by NETs can prevent the spread of pathogens and effectively kill and eliminate pathogens. However, the components of NETs can also abnormally activate the coagulation pathway and participate in the formation of pathological thrombi. This review aims to summarize the mechanisms of NETs formation in detail; the research progress of NETs in venous thrombosis, arterial thrombosis, acquired disease-associated thrombosis, sepsis coagulation disorder; as well as the strategies to target NETs in thrombosis prevention and treatment.